Remote Classes During the Pandemic: difficulties and strategies used by parents - Nataly Moretzsohn Silveira Simões Lunardi; Andrea Nascimento; Jeff Barbosa de Sousa; Núbia Rafaela Martins da Silva; Teresa Gama Nogueira Pereira; Janaína da Silva Gonçalves Fernandes (Universidade Federal do Rio Grande do Sul, 2021)
The research's objective is to understand the social representations of parents about their difficulties and offered to their children. 147 parents/guardians of children in remote education participated. For data collection, a sociodemographic questionnaire and Free Word Evocation Test were used. The data were analyzed using prototypical analysis. The results showed difficulties with the internet, time management, concentration, and reconciliation of the study/work. The strategies adopted were: organization of the routine and the workplace and study, conversations, and monitoring of the children's activities. It was considered that these parents need more information and better school support.